Telessaúde : avaliação de radiografias por dispositivos móveis do terço médio da face em CTBMF - Zanella, Thiago Aragon (2016)
Introduction: The first objective of telehealth is to promote contact between doctor and patient for the population in distant locations witch would not receive this medical attention otherwise. Telemedicine reduces time and distance in communication between patient and health professional. With the creation e mass use of smartphones due to their low cost and great public, various communication applications were created, the main one being WhatsApp messenger. With all these advances the potential for health evaluation greatly increased e new studies are necessary for validation of these technologies. Objective: Evaluate de use of mobile devices (smartphones) in the acquisition of photographs of radiographic films e their validation in interpretation for diagnosis of midface fracture (Waters view) in different remote instruments (tablets and smartphones). Methods: Forty occiptomental radiographs were selected and photographed in a lightbox by a mobile device (smartphone). The images where then sent to another smartphone through the WhatsApp application and to a tablet through e-mail. The evaluators were questioned about the presence of fracture and its location in both mobile devices and by the conventional method on the lightbox. Results: Both devices presented significant sensibility and specificity predicting positive and negative values. There was excellent agreement between two observers e medium for one observer. The tablet presented better results in the interpretation of the images. Conclusion: The use of the tablet for interpretation of the images send through e-mail (original size) obtained better results. Although the compression of the images fulfilled by the WhatsApp app the smarphone can be used for interpretation of mid face fractures.